Superalloys 2012 (Twelfth International Symposium) 2012
DOI: 10.7449/2012/superalloys_2012_149_158
|View full text |Cite
|
Sign up to set email alerts
|

Grain Boundary Deformation and Fracture Mechanisms in Dwell Fatigue Crack Growth in Turbine Disk Superalloy ME3

Abstract: The objective of this paper is the development of a multiscale, mechanistic based intergranular crack growth model, which considers creep, fatigue and environment interactions in a nickel disk material, ME3. In this model, the basic cracking mechanism involves grain boundary (GB) sliding and dynamic embrittlement, which are identified by examining the apparent activation energy, as well as, the slip/GB interactions in both air and vacuum environments. Modeling of the damage events is achieved by adapting a coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…It is widely reported that the addition of a dwell period at maximum load at high temperature can significantly increase the crack growth rate per fatigue cycle in Ni-base superalloys [40][41][42][43][44][45][46][47][48][49][50][51][52]. Among these literature, Gustafsson et al [51,[53][54][55] has reported systematic results on the crack propagation behaviours with different dwell periods at different temperatures of a forged IN718.…”
Section: Accelerated Crack Propagationmentioning
confidence: 99%
“…It is widely reported that the addition of a dwell period at maximum load at high temperature can significantly increase the crack growth rate per fatigue cycle in Ni-base superalloys [40][41][42][43][44][45][46][47][48][49][50][51][52]. Among these literature, Gustafsson et al [51,[53][54][55] has reported systematic results on the crack propagation behaviours with different dwell periods at different temperatures of a forged IN718.…”
Section: Accelerated Crack Propagationmentioning
confidence: 99%